A process for the development of a psychosocial educational programme to facilitate the reintegration of incarcerated women who had dumped babies and / or committed infanticide in Namibia - Sumpi, Ndempavali; Amukugo, Hans Justus (International Journal of Health, 2016)
The aim of this paper is to describe the steps/process used to develop a psychosocial educational programme to facilitate the reintegration of incarcerated women who had dumped babies and / or committed infanticide in Namibia. This process was done in four phases namely Phase 1, was carried out to explore and describe the lived experiences of women who had dumped and / or committed infanticide. The researcher used in-depth unstructured individual interviews for data collection and data was analysed by using Tech’s method of qualitative data analysis. Phase 2, focuses on the conceptualisation framework guided the development of a psychosocial educational programme that facilitated the reintegration process of women who had dumped and / or committed infanticide. The educational programme included the activities suggested in the survey list of Dickoff et al. (1968); namely, agent, recipient, context, dynamics, procedures, and terminus. Phase 3, focused on the development of a psychosocial educational programme to facilitate the reintegration process of women who had dumped their babies and / or committed infanticide. The survey list of Dickoff et al. (1968) was adopted as a reasoning map in the construction of the development of a psychosocial educational programme, as well as the findings of the situational analysis of this study. And Phase 4, focused on the implementation and evaluation of the psychosocial educational programme that was developed to facilitate the reintegration of incarcerated women who had dumped babies and / or committed infanticide. A three-day training workshop was held at the Oluno Correctional Facility to conduct the educational programme. The educational programme was evaluated in order to validate whether the programme interventions were likely to bring about the desired change among the participants.A process for the development of a psychosocial educational programme to facilitate the reintegration of incarcerated women who had dumped babies and / or committed infanticide in Namibia